Implementation of ezTrack open-source pipeline for quantifying rat locomotor behavior: Comparison to commercially available software. (1st April 2020) - McElroy, Dan L.; Roebuck, Andrew J.; Onofrychuk, Timothy J.; Sandini, Thaísa M.; Greba, Quentin; Howland, John G.
Highlights: ezTrack open source software was compared to commercial behavioral tracking software in elevated plus maze and open field. The software packages provided similar results for locomotor activity in time spent in a region of interest. ezTrack is a viable alternative to commercial software for these measures of rat behavior. Abstract: Animal tracking software is an important tool to record and analyze locomotor activity during behavioral assays that provides considerable advantages over traditional manual scoring approaches (e.g., counting line crosses on a grid overlay or using a stopwatch to score time spent in regions of interest). Although several options are available to researchers, tracking software is often costly or requires advanced technical knowledge to operate efficiently. In this study, a free open-source behavioral tracking pipeline called ezTrack was compared to commercially available software for assessing rat locomotor behavior and time spent in regions of interest during elevated plus maze (EPM) and open field test (OFT) assays. ezTrack produced nearly identical results to the commercial software. Overall, these results suggest that ezTrack is a cost-effective approach to quantify some aspects of behavior in these tasks.